Pengaruh Motivasi Kerja dan Beban Kerja terhadap Kinerja Pegawai ASN pada Badan Pendapatan Daerah Kota Bogor - Andia Janash Mumthaza; Afriyanti Eva Belinda Lase; Irfan Achmad Musadat; Niken Widyastuti; Harianto Simarmata (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to determine the description of work motivation, workload, and employee performance, as well as to analyze the magnitude of the influence of work motivation and workload on employee performance, both partially and simultaneously. The research method used is descriptive and verification with a quantitative approach. The study population includes all employees of the Bogor City Regional Revenue Agency, namely 83 ASN, who were used as respondents using a non-probability sampling technique through a saturated sampling approach. The results of the study indicate that the description of work motivation, workload, and employee performance are generally included in the sufficient category. Based on the results of the determination test, it is known that work motivation has a 53.5% effect on employee performance, while workload has a 13.9% effect on employee performance. Simultaneously, work motivation and workload have a 61.9% effect on employee performance. Thus, the results of the hypothesis test prove that work motivation and workload have a significant effect on employee performance.